Measuring Disaster Crop Production Losses Using Survey Microdata : Evidence from Sub-Saharan Africa - Markhof, Yannick Valentin; Ponzini, Giulia; Wollburg, Philip Randolph (Washington, DC: World Bank, 2022)
Every year, disasters account for billions of dollars in crop production losses in low- and middle-income countries and particularly threaten the lives and livelihoods of those depending on agriculture. With climate change accelerating, this burden will likely increase in the future and accurate, micro-level measurement of crop losses will be important to understand disasters’ implications for livelihoods, prevent humanitarian crises, and build future resilience. Survey data present a large, rich, highly disaggregated information source that is trialed and tested to the specifications of smallholder agriculture common in low- and middle-income countries. However, to tap into this potential, a thorough understanding of and robust methodology for measuring disaster crop production losses in survey microdata is essential. This paper exploits plot-level panel data for almost 20,000 plots on 8,000 farms in three Sub-Saharan African countries with information on harvest, input use, and different proxies of losses; household and community-level data; as well data from other sources such as crop cutting and survey experiments, to provide new insights into the reliability of survey-based crop loss estimates and their attribution to disasters. The paper concludes with concrete recommendations for methodology and survey design and identifies key avenues for further research.